1998
DOI: 10.1021/ic980192n
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide(III) Complexes of Tripodal N-Donor Ligands:  Structural Models for the Species Involved in Solvent Extraction of Actinides(III)

Abstract: The complexation of lanthanides(III) by the tripodal ligands tpa (tris[(2-pyridyl)methyl]amine) and tpza (tris[(2-pyrazinyl)methyl]amine) has been investigated by solution NMR studies and by X-ray crystallography. The crystallographic studies show that both tpa and the new ligand tpza form complexes with a 1:1 metal:ligand ratio in which the tripodal amine acts as a tetradentate ligand. For the tpa complexes the remaining coordination sites are occupied by chloride counterions to give 7-coordination (Eu, Tb, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 42 publications
9
121
1
Order By: Relevance
“…Pyridine groups generally coordinate to metal cations by using N-atoms and they are categorized as soft-donor type ligands [14]. It has been reported that pyridine-type N-donor ligands can selectively extract trivalent An from Ln [12,13], suggesting that the pyridine groups have a larger affinity for An than for Ln(III) [15]. On the other hand, trivalent An and Ln cations are tightly hydrated with 8-9 water molecules in aqueous solution [16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Pyridine groups generally coordinate to metal cations by using N-atoms and they are categorized as soft-donor type ligands [14]. It has been reported that pyridine-type N-donor ligands can selectively extract trivalent An from Ln [12,13], suggesting that the pyridine groups have a larger affinity for An than for Ln(III) [15]. On the other hand, trivalent An and Ln cations are tightly hydrated with 8-9 water molecules in aqueous solution [16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…[31] The three arms of the dpaa ligand adopt a pincer-like arrangement around the metal centre, whereas the three picolinate arms adopt a helical arrangement in the tpaa 3À complex. This behaviour does not lead to significant differences in the Lu À O carboxy bond length (mean values: 2.27(2) and 2.30(4) in LuA C H T U N G T R E N N U N G (dpaa) and LuA C H T U N G T R E N N U N G (tpaa), respectively) and the Lu À N bond length (mean values: 2.46(1) and 2.48 (9) in LuA C H T U N G T R E N N U N G (dpaa) and LuA C H T U N G T R E N N U N G (tpaa), respectively).…”
Section: Synthesismentioning
confidence: 99%
“…The compositions of the studied solutions and relaxivity values are reported in the Supporting Information. The theoretical expressions given by Equation (33) of the mean relaxivities r 1 and r 2 , derived in the Theory section, with the equilibrium concentration [C] eq of the free complex given by Equation (31), were fitted to their experimental counterparts. The theoretical mean relaxivities r 1 and r 2 are displayed in Figure 6 for selected values of n BSA = 2, 4, 10 and 20 and associated formation constants per site k = 1300, 360, 110 and 50 L mol À1 , which are compatible with the experimental value of q .…”
Section: Interactions Of [Gda C H T U N G T R E N N U N G (Dpaa)a C Hmentioning
confidence: 99%
“…They also form stable lanthanide complexes exhibiting characteristic luminescence properties [8][9][10][11]. Mazzanti and co-workers determined the crystal structure of EuCl 3 complex with parent tris(2-pyridylmethyl)amine 5, in which three Cl − anions directly coordinated with the Eu 3+ center together with four nitrogen atoms of the ligand [8]. A few chiral versions of tris(2-pyridylmethyl)amine have recently been reported.…”
Section: Tripodal Ligands For Lanthanide Complexationmentioning
confidence: 99%
“…Mazzanti and co-workers characterized 1:1 complexes between tripode 5 and some lanthanide chlorides [8]. Their X-ray crystallographic studies revealed that four nitrogen atoms effectively coordinated with the lanthanide cation.…”
Section: Lanthanide Complexes With Stereo-controlled Ligandsmentioning
confidence: 99%